Evaluation of DistilBERT and BiLSTM Models for the Development of Islamic Chatbots Based on Tag Classification - Muhammad Rizki Al-Fathir; Muhammad Saifurridwani 'Ijazi; Nabila Lailatanzila; Nirwan Rasyid Ridlo; Riza Anwar Fadil (Khazanah Journal of Religion and Technology, 2026)
This study evaluates the performance of DistilBERT and Bidirectional Long Short-Term Memory (BiLSTM) models for intent classification in Islamic chatbots, with the main challenge being a highly imbalanced dataset containing 2,031 unique intents. Following the CRISP-DM methodology, the DistilBERT model was fine-tuned using Focal Loss to address class imbalance, while the BiLSTM model was built from scratch with a standard loss function. The evaluation results demonstrated the absolute superiority of DistilBERT, achieving an accuracy of 65.15%, far surpassing BiLSTM, which achieved only 34.50% due to severe overfitting. Although the final model sizes of both were similar, DistilBERT training proved to be significantly more efficient. These findings demonstrate that a Transformer-based architecture combined with an appropriate strategy, such as Focal Loss, is a much more robust and effective solution for large-scale, imbalanced text classification in specific domains. The practical feasibility of this approach was validated through its successful implementation in a publicly accessible, functional chatbot prototype.